2014
DOI: 10.3390/ijms150610215
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Functional Analysis of the Peroxiredoxin Specifically Expressed in Bursaphelenchus xylophilus—The Causative Agent of Pine Wilt Disease

Abstract: The pine wood nematode, Bursaphelenchus xylophilus, is the causal agent of pine wilt disease. Accurately differentiating B. xylophilus from other nematodes species, especially its related species B. mucronatus, is important for pine wood nematode detection. Thus, we attempted to identify a specific protein in the pine wood nematode using proteomics technology. Here, we compared the proteomes of B. xylophilus and B. mucronatus using Two-dimensional gel electrophoresis (2-DE) and matrix-assisted laser desorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…Silencing of CePrx2 in C. elegans resulted in a stunted development and a significantly reduced brood size 32 . Similarly, knocking down BxPrx significantly reduced the propagation in B. xylophilus 50 . Our previous study found that anti-serum of BxPrx could only detect protein samples extracted from virulent B. xylophilus but not B. mucronatus 28 , suggesting that BxPrx could be used as a molecular marker to identify the virulent B. xylophilus 50 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Silencing of CePrx2 in C. elegans resulted in a stunted development and a significantly reduced brood size 32 . Similarly, knocking down BxPrx significantly reduced the propagation in B. xylophilus 50 . Our previous study found that anti-serum of BxPrx could only detect protein samples extracted from virulent B. xylophilus but not B. mucronatus 28 , suggesting that BxPrx could be used as a molecular marker to identify the virulent B. xylophilus 50 .…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, knocking down BxPrx significantly reduced the propagation in B. xylophilus 50 . Our previous study found that anti-serum of BxPrx could only detect protein samples extracted from virulent B. xylophilus but not B. mucronatus 28 , suggesting that BxPrx could be used as a molecular marker to identify the virulent B. xylophilus 50 . A shorter life cycle and higher proliferation rate are the fundamental differences between avirulent and virulent B. xylophilus , therefore, BxPrx could play a role in the pathogenicity of B. xylophilus .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Three copies of the twitching motility gene pilT were annotated in the UFV-E1 genome, important for spreading pathogen cells on the surface of the host (Weller-Stuart et al, 2017). Three translated protein sequences from the UFV-E1 genome have shown similarity with catalase-peroxidases and peroxiredoxins from PHI-base (accessions A4QUT2, B0LFQ7 and G4MXC5), enzymes with very important roles in the maintenance of redox homeostasis and the protection of pathogen cells from oxidative damage brought by hydrogen peroxide produced by host cells (Tanabe et al, 2011;Fu et al, 2014;Mir et al, 2015;Santander, Figàs-Segura & Biosca, 2018). Genes for other proteins potentially involved in detoxification have also been predicted, including multidrug efflux pumps (D4HXR8 and Q7WTQ9), which may confer resistance to phytoalexins (Burse, Weingart & Ullrich, 2004), and S-(hydroxymethyl)gluthatione dehydrogenase (G4N4N6), which is produced by phytopathogens as protection against damage from nitric oxide (Zhang et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…The availability of the completely sequenced genome of B. xylophilus has opened up the possibility of investigating the most prominent proteins that play a crucial role in the survival and parasitism of the nematode as novel drug targets [ 16 , 17 ]. Hence in this study, cathepsin L-like cysteine proteinase that is involved in post embryonic development [ 18 ], 2-cysteine peroxiredoxins that regulates reproduction and pathogenecity [ 19 ], heat shock protein 90 (HSP90) that helps adaptation to different climatic conditions [ 20 ], venom allergen proteins (VAP) that manifests the invasion of parasitic genes [ 21 ] and tubulin that regulates the microtubule, mitosis and motility [ 22 , 23 ] of B. xylophilus are considered as drug targets. In general, the anti-nematode drugs are classified into two main types based on their target sites, such as drugs targeting membrane ion channels and other class of drugs that acts on biochemical targets.…”
Section: Introductionmentioning
confidence: 99%